Aspek kemahiran ‘employability’ yang dikehendaki majikan industri pembuatan masa kini - Mohamad Sattar Rasul; Md Yusof Ismail; Napsiah Ismail; Rashid Rajuddin; Roseamnah Abd. Rauf (penerbit ukm, 2009)
Employability skill is one of the skills that employers need. This study is to identify important aspects of employability skills needed by the manufacturing industries employer of their workers especially new workers. Samples for the research consist of 107 employers from manufacturing industry and this study has been done to two types of company, according to categories which is size and ownership status. Analysis of the survey done, manage to determine important aspects of the employability skills needed by employers in the manufacturing industries. The skills were ranked and results shows that the basic skill, thinking skill, sources skill, resources skill, system and technology skill and personal qualities are the most important skills that employers need compare to informational skill which is less important. From the research findings, graduates can identify important aspect of employability skills to focus in enhancing their marketability before entering working environment. As for institutions, the employability skills listed will help to focus inculcating which employability skills to stress in their teaching and learning process.